APLIKASI MACAM PUPUK KANDANG DAN PUPUK DAUN PADA HASIL TANAMAN TERONG (Solanum melongena, L.) VARITAS ANTABOGA (Universitas Tidar, 2019)
A research on the application of kinds of manure and foliar fertilizer on eggplant yield (Solanum melongena, L.) Antaboga variety. The research conducted in March until July 2018. Location of research in Kliwonan, Sukomulyo, Kajoran Magelang. The latitude is 660 m. The soils is latosol with pH 6,6. The research method use factorial experiment (3x3) arranged in a randomized complete block design with repeated three times. The first factor is kinds of manure, cow manure, chicken manure, and goat manure. The second factor is kinds of foliar fertilizer, Gandasil B, Topsil B, and Neo Kristalon. The results of the research show that chicken manure increases the plant height, number of fruit per plant, fruit weight per plant, and fresh weight of stover per plant. Neo Kristalon increases plant height. Different manure on different foliar fertilizer give regular respond on all observed parameters.